Spiritualitas di Kehidupan Modern dalam Film Animasi Tiongkok Little Door Gods (2016) - Prawira, Mentari Putrirahayu; Haryanto, Haryanto; Bajuri, M. Zahrul Jihadurrohim (Nitisara: Jurnal Ilmu Bahasa, 2024)
In contemporary times, rationalism has emerged as the fundamental principle of thinking, leading to the neglect of spiritual matters by society. The portrayal of this concept can be observed in the Chinese animated film called Little Door Gods (2016), helmed by director Gary Wang. This study seeks to examine how the animated film "Little Door gods" portrays spirituality in contemporary society. This study use the Boggs and Petrie film theory (2017) to examine the progression and context of the film narrative, which serves as the research data. Barthes's semiotic theory, introduced in 1972, is also employed to analyse the symbols found in films. This study observes that the film utilises Chinese culture or Chinese mythology as a foundation for its narrative. There exists a correlation between the realm of humans and the realm of deities, which demonstrates that human spirituality has an impact on the divine realm. Additionally, this relationship portrays the gradual decline of spirituality in contemporary society. Mythology, in its origins, encompassed both a cultural framework and a system of beliefs. In the contemporary age, it also served as a means to harmonise significant occasions. The video also makes an effort to familiarise children with Chinese mythology.